The Death of Skepticism or San Augustine and Academics - Gonzalo (Estudios de Filosofía, 2002)
This article intends to show the contradictions in which the academic incurs with his statement: “there is no truth, all goes ". Augustine argues that this skeptical thesis knocks down both knowing and acting, and endangers the living together of mankind. The article concludes by proving that friendship and mystical way of life are arguments against academics.